Easy to guess, somewhat hard to prove!

Algebra Level 2

If x 2 x^{2} + a 2 a^{2} = y 2 y^{2} + b 2 b^{2} = ( a × x a\times x ) + ( b × y b\times y ) = 1,

then the numerical value of a 2 a^{2} + b 2 b^{2} is


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Jaiveer Shekhawat
Nov 13, 2014

x 2 x^{2} + a 2 a^{2} = 1

y 2 y^{2} + b 2 b^{2} = 1

x 2 x^{2} + a 2 a^{2} + y 2 y^{2} + b 2 b^{2} = 2

x 2 x^{2} + a 2 a^{2} + y 2 y^{2} + b 2 b^{2} = 2(( a × x a\times x ) + ( b × y b\times y ))

x 2 x^{2} + a 2 a^{2} + y 2 y^{2} + b 2 b^{2} - 2( a × x a\times x ) - 2( b × y b\times y ) = 0

( x a ) 2 (x-a)^{2} + ( y b ) 2 (y-b)^{2} = 0

x = a x = a ; y = b y = b

therefore,

x 2 x^{2} + a 2 a^{2} = 1

a 2 a^{2} + a 2 a^{2} = 1

2 a 2 a^{2} = 1

thus, a 2 a^{2} = 1 2 \frac{1}{2}

similarly , b 2 b^{2} = 1 2 \frac{1}{2}

thus,

a 2 a^{2} + b 2 b^{2} =1

One more method ,

x = s i n A , y = s i n B x = sinA , y = sinB

U Z - 6 years, 6 months ago

Log in to reply

I did it the same way to reach answer.

A good way of using trigonometry to get algebraic results. Yesterday I also saw one problem of algebra solved with the help of geometry. I like such mixing. It allows you to think differently which is outside the domain of any kind of school/coaching syllabus.

Love Math, Love Brilliant!!

Ninad Akolekar - 6 years, 6 months ago

Easy to guess = Easy in brilliant

lol

math man - 6 years, 7 months ago

From Cauchy Schwarz's inequality, we get

( a × x + b × y ) 2 ( a 2 + b 2 ) ( x 2 + y 2 ) (a\times x + b\times y)^{2} \leq \left(a^{2}+b^{2}\right)\left(x^{2}+y^{2}\right)

Since x 2 + a 2 + y 2 + b 2 = 2 x^{2}+a^{2}+y^{2}+b^{2} = 2 , we get x 2 + y 2 = 2 ( a 2 + b 2 ) x^{2}+y^{2} = 2-\left(a^{2}+b^{2}\right)

Substitute back into inequality we get

1 ( a 2 + b 2 ) ( 2 ( a 2 + b 2 ) ) 1 \leq (a^{2}+b^{2})(2-(a^{2}+b^{2}))

( ( a 2 + b 2 ) 1 ) 2 0 ((a^{2}+b^{2})-1)^{2} \leq 0

But for any real number k k , k 2 0 k^{2} \geq 0 .

Therefore, a 2 + b 2 1 = 0 a^{2}+b^{2}-1 = 0 is the only case.

Which gives a 2 + b 2 = 1 a^{2}+b^{2} = \boxed{1} ~~~

In similar ways, we also get x 2 + y 2 = 1 x^{2}+y^{2} = 1 .

Using Cauchy-Schwarz inequality:

x 2 + a 2 2 a x y 2 + b 2 2 b y x 2 + a 2 + y 2 + b 2 2 a x + 2 b y x^{ 2 }+a^{ 2 }\ge 2ax\\ { y }^{ 2 }+{ b }^{ 2 }\ge 2by\\ \Rightarrow x^{ 2 }+a^{ 2 }+{ y }^{ 2 }+{ b }^{ 2 }\ge 2ax+2by

As a x + b y = 1 ax + by = 1 , we obtain: x 2 + a 2 + y 2 + b 2 2 x^{ 2 }+a^{ 2 }+{ y }^{ 2 }+{ b }^{ 2 }\ge 2

Since x 2 + a 2 = y 2 + b 2 = 1 { x }^{ 2 }+{ a }^{ 2 }={ y }^{ 2 }+b^{ 2 }=1 , which means x 2 + a 2 + y 2 + b 2 = 2 { x }^{ 2 }+{ a }^{ 2 }+{ y }^{ 2 }+b^{ 2 }=2 , the equal sign must occur for each inequality mentioned above.

Hence: x = a , y = b x=a, y=b

x 2 + a 2 + y 2 + b 2 = 2 ( a 2 + b 2 ) = 2 x^2 + a^2 + y^2 + b^2 = 2({a^2 + b^2})=2

a 2 + b 2 = 1 a^2 + b^2 = 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...